2002
DOI: 10.1006/viro.2002.1462
|View full text |Cite
|
Sign up to set email alerts
|

Viremia and Immunogenicity in Nonhuman Primates of a Tetravalent Yellow Fever–Dengue Chimeric Vaccine: Genetic Reconstructions, Dose Adjustment, and Antibody Responses against Wild-type Dengue Virus Isolates

Abstract: Chimeric yellow fever (YF)-dengue (DEN) viruses (ChimeriVax-DEN) were reconstructed to correct amino acid substitutions within the envelope genes of original constructs described by Guirakhoo et al. (2001, J. Virol. 75, 7290-7304). Viruses were analyzed and compared to the previous constructs containing mutations in terms of their growth kinetics in Vero cells, neurovirulence in mice, and immunogenicity in monkeys as monovalent or tetravalent formulations. All chimeras grew to high titers [ approximately 7 to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
80
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 136 publications
(84 citation statements)
references
References 22 publications
4
80
0
Order By: Relevance
“…The lower dose (3.0 log 10 PFU) was selected based on preclinical data in nonhuman primates: a tetravalent formulation containing all 4 chimeric viruses required a 3-log dose of ChimeriVax™-DEN2 and a higher dose of the other 3 viruses to avoid possible interference effects. 9 Adverse events were anticipated to resemble those associated with ChimeriVax™-JE. Data from Phase 1 and 2 trials of this vaccine indicated that it was well tolerated and highly immunogenic at all dose levels tested (5.8 to 1.8 log 10 PFU).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The lower dose (3.0 log 10 PFU) was selected based on preclinical data in nonhuman primates: a tetravalent formulation containing all 4 chimeric viruses required a 3-log dose of ChimeriVax™-DEN2 and a higher dose of the other 3 viruses to avoid possible interference effects. 9 Adverse events were anticipated to resemble those associated with ChimeriVax™-JE. Data from Phase 1 and 2 trials of this vaccine indicated that it was well tolerated and highly immunogenic at all dose levels tested (5.8 to 1.8 log 10 PFU).…”
Section: Discussionmentioning
confidence: 99%
“…7 ChimeriVax™-DEN2 is a live, attenuated, genetically engineered virus prepared by replacing the genes encoding the two structural proteins, premembrane (prM) and envelope (E), of the YF 17D vaccine virus with the corresponding genes of the DEN2 virus (strain PUO-218, isolated from a case of classical DF, Bangkok, Thailand). 8 It is a monovalent component of a tetravalent vaccine formulation 9 currently being investigated in a Phase 2 study. Preclinical studies have demonstrated that the ChimeriVax™-DEN2 virus was is not neurovirulent when administered to adult mice via the intracerebral (IC) route, is genetically stable in cell culture, induces low levels of viremia, and protects 100% of monkeys against wt DEN2 heterologous challenge upon a single SC immunization.…”
Section: Introductionmentioning
confidence: 99%
“…Improved molecular virology techniques and an improved understanding of the genomic structure of DENV have permitted a more rapid approach based on engineering of attenuating mutations into infectious cDNA clones of each of the four DENV serotypes, with the added theoretical advantage of a lower possibility of reversion to virulence (18)(19)(20). Another molecular approach being utilized is the creation of four separate infectious chimeric flaviviruses, each of which contains the pre-M and E genes of one of the four DENV serotypes in a single "backbone" containing the C and NS proteins of an attenuated flavivirus, either the yellow fever vaccine strain or an attenuated DENV strain (21,22). DNA vaccines consisting of plasmids expressing one or a few proteins from each DENV serotype are in an earlier stage of development, as are subunit vaccines based on purified recombinant DENV proteins (23,24).…”
mentioning
confidence: 99%
“…Most of these chimeric viruses are derived from the infectious clone of YF17D (44). YF17D has been used as a "vector" for engineering new vaccines against other flaviviruses (e.g., the ChimeriVax vaccines ChimeriVax-JE [9,37] and ChimeriVax-DEN1, -2, -3, and -4 [13][14][15][16] and other chi-meras, i.e., WN/YF17D [34,35] and DEN2/YF17D, that are based on other dengue type 2 virus strains than the one used for ChimeriVax-DEN2 [5,49]). …”
mentioning
confidence: 99%